Monitoring The Correlation of Climatics to The Airborne Bacteria at The Manggarai Station, South Jakarta, Indonesia - Anindita, Reza; Rahmawati, Auliya; Inggraini, Maulin; Perwitasari, Melania; Nathalia, Dede Dwi; Beandrade, Maya Uzia; Putri, Intan Kurnia (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The highest of microorganisms suspended in the air were bacteria with a percentage of 80.8%. If the intensity of bacterial exposure occurs in large quantities, it will accumulate in the respiratory tract which has the potential to trigger allergic reactions and respiratory infections. Given the problems and impacts caused by air microorganisms on public health, it is necessary to monitor the distribution of air bacteria. The purpose of this study was to determine the relationship between temperature and humidity with the number of bacteria in the Manggarai station area. Type of research is correlation. The sampling location is Manggarai Station, East Jakarta, Indonesia. The 10 sampling points in this study include the station hall, motorbike parking, prayer rooms, train platform 1-2, train platform 2-3, train platform 3-4, and train platform 5, toilet, and underpass. The results of this study included the highest number of bacteria found in the station hall 331 colonies, the highest percentage of bacterial morphology is monobacilli was 78%, the distribution of gram positive was more than gram negative with spore bacteria being more dominant than non spore. The correlation coefficient between temperature and number of bacterial colonies (0.134) and humidity with number of bacterial colonies (0.380) showed weak positive correlation, while the correlation coefficient for light intensity with the number of bacterial colonies -0.140 (very weak negative).